The Development of Educational Practices for Children with Dyslexia in Indonesia - Widyanti Shintya Anggraeni; Wiwin Hendriani (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2022)
Many parents are unaware that their child has dyslexia or commonly known as a learning disability. Dyslexia itself involves difficulty understanding letters and words, resulting in the child being unable to spell or read and write, and because of parental ignorance, the child may need educational and emotional support from teachers and parents. Despite being a special child who needs both of their needs, they are labeled stupid. The purpose of this study is to educate parents that there are many ways that both teachers and parents can teach dyslexic children. This study uses journal literature research methods and descriptive analysis using a variety of methods such as the syllable method, the Glass Analysis method, the multisensory method, and the Fernald method.